Synergy of Collaboration Between BNN and Polri in the Process of Investigating Narcotics Crimes (A Study of the Police and BNN of Southeast Sulawesi Province ) - Yusuf, Muh.; A. Siregar, Winner; Khayati, Sri; Hardiansyah B., LD. Muh. Isman; Umar, Agus; Riyanto, Slamet (International Journal of Management and Education in Human Development, 2023)
Indonesia is a country based on law, not a country based on power. The logical consequence of the principle of the rule of law is that everything in Indonesia must be regulated by a set of statutory regulations. The aim is to create public order towards a society that is physically and mentally prosperous. Legislation regulates individual rights and obligations as citizens. The narcotics problem is a classic problem but is still a big obstacle in law enforcement and national development. Criminal acts are no longer carried out in secret but are carried out very openly by users and dealers in carrying out dangerous goods operations. The fact that can be seen, almost every day, both through print and electronic media, is that these illicit goods have spread everywhere indiscriminately, especially among the teenage generation who are expected to become the nation's next generation in the future. This research lasted for 2 months. This research took place at the Kendari City Police Office and the Regional National Narcotics Agency (BNN). The type of research used is qualitative descriptive research. Based on the research results, several factors found in this research indicate the underlying variables in the framework of building a law enforcement system in relation to social welfare interests and security interests, namely the role of law enforcement in creating legal effectiveness is essentially determined more by 2 (two) ) factor, namely the importance of criminal sanctions so that they can have a deterrent effect and the second factor is the use of appropriate investigative techniques, such as covert purchasing techniques, supervised delivery of narcotics. That the existence of cooperation in the form of an Integrated Assessment Team (TAT) consisting of BNN, Polri, Prosecutor's Office, Supreme Court and Ministry of Law and Human Rights as the legal team while Doctors and Psychologists as the medical team, is very effective in facilitating the process of handling narcotics addicts and victims of narcotics abuse into rehabilitation institution. Obstacles that are often faced in the collaboration process between BNN and Polri are the limited quality of human resources in preventing and taking action against perpetrators of narcotics crimes, both BNN and Polri, the limited number of members owned by BNN, and the limited tools they have in preventing and take action against perpetrators of narcotics crimes.